S.A.S are you Tough Enough? : The Real Story Behind SAS Selction - Davies, Barry (London Boxtree, 2001)
SAS selection is one of the toughest military courses in the world. It involves physical training one would expect to find in an Olympic athlete. It entails stretching the mind and body for the countless techniques the SAS soldier must learn, from weapons, survival and escape to parachuting, interrogation training and hostage rescue. "The BBC" series "SAS - Are You Tough Enough?" tests part of this gruelling selection procedure on thirty members of the public who are put through two weeks of hell in a bid to see who is tough enough for the world's elite regiment. Presented by Dermot O'Leary, the series starts with an initial elimination process, and the pressure is relentless as physically and mentally they are tested to the limit. Everything is designed to test their willpower and there are no second chances - one slip and they're out. First published as "Joining the SAS", this book provides a rare insight into the SAS' legendary training and covers how to get fit enough, how to conduct yourself and what you can expect when you enter a squadron. With photographs of the BBC consultants in action, "SAS - Are You Tough Enough?" provides an analysis of how the volunteers coped with the course as well as a full picture of SAS selection and what life is really like in the most respected and feared Special Forces unit in the world.
Include Color IIIustrations, Note and Index
Keywords: Great Britain -- Great Britain. Army. Special Air Service -- Basic training (Military education)